Динаміка роботи підйомно-транспортних машин з сипкими матеріалами - Зінько, Роман; Крайник, Любомир; Горбай, Орест (Видавництво Львівської політехніки, 2018)
Municipal machine operate under conditions that are significantly different from the operating conditions of trucks. The use of trucks frame, whose load modes are different from the operating modes of utility vehicle, often leads to it destruction at long time before the expiration the service life. A set of virtual tests was developed. It allowed to effectively control the strength and durability of frames of utility vehicles and their individual parts at all stages of designing. That allowed to analyze the strength of the municipal machine frame and do the structural modernization too.
Functioning of industrial vehicle with bulks material
Keywords: 629.341